Assessing long-term effectiveness and cost-effectiveness of statin therapy in the UK: a modelling study using individual participant data sets - Borislava Mihaylova; Runguo Wu; Junwen Zhou; Claire Williams; Iryna Schlackow; Jonathan Emberson; Christina Reith; Anthony Keech; John Robson; Richard Parnell; Jane Armitage; Alastair Gray; et al. (Health Technology Assessment)
Background Cardiovascular disease has declined but remains a major disease burden across developed countries. Objective To assess the effectiveness and cost-effectiveness of statin therapy across United Kingdom population categories. Design The cardiovascular disease microsimulation model, developed using Cholesterol Treatment Trialists’ Collaboration data and the United Kingdom Biobank cohort, projected cardiovascular events, mortality, quality of life and healthcare costs using participant characteristics. Setting United Kingdom primary health care. Participants A total of 117,896 participants in 16 statin trials in the Cholesterol Treatment Trialists’ Collaboration; 501,854 United Kingdom Biobank participants by previous cardiovascular disease status, sex, age (40–49, 50–59 and 60–70 years), 10-year cardiovascular disease risk [QRISK®3 (%): < 5, 5–10, 10–15, 15–20 and ≥ 20] and low-density lipoprotein cholesterol level (< 3.4, 3.4–4.1 and ≥ 4.1 mmol/l); 20,122 United Kingdom Biobank and Whitehall II participants aged ≥ 70 years by previous cardiovascular disease status, sex and low-density lipoprotein cholesterol (< 3.4, 3.4–4.1 and ≥ 4.1 mmol/l). Interventions Lifetime standard (35–45% low-density lipoprotein cholesterol reduction) or higher-intensity (≥ 45% reduction) statin. Main outcome measures Quality-adjusted life-years and incremental cost per quality-adjusted life-year gained from the United Kingdom healthcare perspective. Data sources Cholesterol Treatment Trialists’ Collaboration and United Kingdom Biobank data informed risk equations. United Kingdom primary and hospital care data informed healthcare costs (2020–1 Great British pounds); £1.10 standard or £1.68 higher-intensity generic statin therapy per 28 tablets; and Health Survey for England data informed health-related quality of life. Meta-analyses of trials and cohort studies informed the effects of statin therapies on cardiovascular events, incident diabetes, myopathy and rhabdomyolysis. Results Across categories of participants 40–70 years old, lifetime use of standard statin therapy resulted in undiscounted 0.20–1.09 quality-adjusted life-years gained per person, and higher-intensity statin therapy added a further 0.03–0.20 quality-adjusted life-years per person. Among participants aged ≥ 70 years, lifetime standard statin was estimated to increase quality-adjusted life-years by 0.24–0.70 and higher-intensity statin by a further 0.04–0.13 quality-adjusted life-years per person. Benefits were larger among participants at higher cardiovascular disease risk or with higher low-density lipoprotein cholesterol. Standard statin therapy was cost-effective across all categories of people 40–70 years old, with incremental costs per quality-adjusted life-year gained from £280 to £8530. Higher-intensity statin therapy was cost-effective at higher cardiovascular disease risk or higher low-density lipoprotein cholesterol. Both standard and higher-intensity statin therapies appeared to be cost-effective for people aged ≥ 70 years, with an incremental cost per quality-adjusted life-year gained of under £3500 for standard and under £11,780 for higher-intensity statin. Standard or higher-intensity statin therapy was certain to be cost effective in the base-case analysis at a threshold of £20,000 per quality-adjusted life-year. Statins remained cost-effective in sensitivity analyses. Limitations The randomised evidence for effects of statin therapy is for about 5 years of treatment. There is limited randomised evidence of the effects of statin therapy in older people without previous cardiovascular disease. Conclusions Based on the current evidence of the effects of statin therapy and modelled contemporary disease risks, low-cost statin therapy is cost-effective across all categories of men and women aged ≥ 40 years in the United Kingdom, with higher-intensity statin therapy cost-effective at higher cardiovascular disease risk or higher low-density lipoprotein cholesterol. Future work Cholesterol Treatment Trialists’ Collaboration has ongoing studies of effects of statin therapy using individual participant data from randomised statin trials. Ongoing large randomised controlled trials are studying the effects of statin therapy in people ≥ 70 years old. Future economic analyses should integrate the emerging new evidence. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 17/140/02) and is published in full in Health Technology Assessment; Vol. 28, No. 79. See the NIHR Funding and Awards website for further award information. Plain language summary Cardiovascular disease, such as heart attack or stroke, is a major cause of death and disability worldwide. Statins, a medication that reduces the level of cholesterol, have been reliably shown to reduce cardiovascular risk. They are available at low cost, are generally safe, and are widely recommended for people with or at increased risk of cardiovascular disease. However, it is uncertain whether the right people in the United Kingdom are recommended to receive this treatment and whether there are further categories of people who can benefit. We set out to assess the benefits and value for money of statins across people in the United Kingdom depending on their sex, age, cholesterol level, whether they already had cardiovascular disease, and if not, their estimated risk of developing it, to resolve remaining uncertainties. We used data from large statin studies and large contemporary United Kingdom population studies to develop a model to predict future cardiovascular disease, mortality, quality of life and healthcare costs for different people with and without statin treatment. We found that all people aged 40 years or older, whether men or women, younger or older, and independent of their level of cholesterol or cardiovascular risk, are highly likely to benefit cost-effectively from statin therapy to reduce their cardiovascular risk. We project that long-term statin treatment would increase people’s length and quality of life, with people at higher cardiovascular risk or with higher levels of cholesterol benefiting most. For most categories, more potent statin regimens that achieve larger cholesterol reductions provide the best value, although standard statin regimens may be enough for men and women at lower cardiovascular risk or with lower cholesterol levels. This study suggests that statin treatment should be strengthened among people at higher cardiovascular risk, and extending statin treatment to further categories of people aged 40 years or older should be considered. Scientific summary Background Despite substantial declines in cardiovascular disease (CVD) morbidity and mortality across high-income countries in recent decades, CVD remains a major disease burden. Across randomised trials, statin therapy has been reliably shown to reduce rates of CVD irrespective of age, sex, CVD risk and comorbidities, with more potent statin regimens achieving larger reductions in low-density lipoprotein cholesterol (LDL-C), demonstrating larger CVD risk reductions. While generally safe, statin therapy has been linked to small excesses in muscle events and incident diabetes. Objectives To develop a reliable evaluative framework, informed by large UK individual participant data (IPD), and to assess the long-term net health effects and cost-effectiveness of statin therapy across a wide range of UK population categories. Methods A CVD microsimulation policy model was developed using the Cholesterol Treatment Trialists’ Collaboration (CTTC) data and the UK Biobank (UKB) cohort data. CTTC IPD and UKB IPD informed parametric proportional hazards risk equations for myocardial infarction (MI), stroke, coronary revascularisation, incident diabetes, incident cancer and vascular and nonvascular death using participant characteristics. UKB and linked UK primary and hospital care data and NHS reference costs informed healthcare costs related to participant characteristics and disease events (2020–1 Great British pounds); £1.10 standard and £1.68 higher-intensity generic statin treatment per 28 tablets. Health Survey for England data informed health-related quality of life (HRQoL) related to participant characteristics and disease events. CTTC IPD meta-analyses and further meta-analyses of trials and cohort studies informed the effects of statin therapies on cardiovascular events and the excess risks of myopathy, rhabdomyolysis and incident diabetes with statin therapy. The net health effects and cost-effectiveness of lifetime standard statin (35–45% LDL-C reduction) and of higher-intensity (≥ 45% LDL-C reduction) statin therapy prescribed and monitored in the UK primary healthcare service were assessed. We report the quality-adjusted life-years (QALYs) gained and incremental cost per QALY gained with the two levels of intensity of statin regimens from the perspective of UK healthcare services across UKB and Whitehall II participants in categories by previous CVD status, sex, age (40–49; 50–59; 60–70, ≥ 70 years), 10-year CVD risk [QRISK®3 (%): < 5; 5–10, 10–15, 15–20, ≥ 20] and/or LDL-C level (< 3.4, 3.4–4.1, ≥ 4.1 mmol/l) at statin therapy initiation. In the base-case analyses, the proportional effects of statin therapy on disease risks were assumed constant across categories of individuals and over time. Key parameters were varied in sensitivity and scenario analyses, including scenarios with hypothetical disutility of daily statin treatment, higher statin cost, and more limited reductions in cardiovascular events with statin therapy. Results A total of 117,896 participants in 16 statin versus control trials in the CTTC, 501,854 UKB participants and 6761 Whitehall II participants informed the analyses. Age, sex, socioeconomic deprivation, smoking, hypertension, diabetes, MI and stroke events were key determinants of CVD risk. Model-predicted event rates corresponded well to observed rates across participant categories in UKB and Whitehall II studies. Modelled CVD and nonvascular disease events were associated with reductions in HRQoL and increases in hospital admission and primary care costs. Across categories of participants 40–70 years old, there were estimated gains in undiscounted QALYs of 0.20–1.09 per person with lifetime use of standard statin therapy, and higher-intensity statin therapy added a further 0.03–0.20 QALYs per person. Among participants aged ≥ 70 years, lifetime use of standard statin increased quality of life-adjusted life expectancy by 0.24–0.70 QALYs and higher-intensity statin by further 0.04–0.13 QALYs per person. Health benefits with statin therapy were larger among participants at higher CVD risk and with higher LDL-C levels. Standard-intensity statin therapy was cost-effective across all population categories 40–70 years old with an incremental cost per QALY gained ranging from £280 to £8530. Higher-intensity statin therapy was cost-effective at higher CVD risk and higher LDL-C levels. Both standard and higher-intensity statin therapies appeared to be cost-effective for people aged ≥ 70 years with an incremental cost per QALY gained below £3500 for standard statin versus no statin and below £11,780 for higher-intensity versus standard statin. Statin therapy, either standard or higher intensity, was found certain to be cost effective at a willingness-to-pay threshold of £20,000 per QALY, with higher-intensity statin therapy preferred at higher CVD risk or higher LDL-C level. The probability of statin therapy being cost-effective remained above 80% across all participant categories at £10,000-per-QALY threshold, albeit with a shift towards a preference for standard statin therapy across some categories of people. Statin therapy remained cost-effective in sensitivity analyses. Limitations The randomised evidence for effects of statin therapy is for duration of statin treatment of about 5 years in trials. There is only limited randomised evidence for effects of statin therapy in older people without previous CVD. In the base-case analysis, it is assumed that statin therapy has a constant proportional effect on CVD risks over lifetime and across different categories of patients. Conclusions Based on current evidence of effects of statin therapy and modelled analyses of contemporary disease risks, low-cost statin therapy is likely to be highly cost-effective across categories of men and women aged ≥ 40 years in the UK, with higher-intensity regimens cost-effective at higher CVD risk or higher LDL-C levels. Future work The CTTC has an ongoing programme of work conducting comprehensive analyses of the effects of statin therapy, both adverse and beneficial, using IPD from randomised controlled trials. In addition, ongoing randomised controlled trials are currently studying the effects of statin therapy in people aged ≥ 70 years. Future economic assessments should integrate this new evidence for effects of statin therapy, both beneficial and adverse, in categories of individuals. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 17/140/02) and is published in full in Health Technology Assessment; Vol. 28, No. 79. See the NIHR Funding and Awards website for further award information.